Vascular Inflammation in Mouse Models of Systemic Lupus Erythematosus - Ryan, Holly; Morel, Laurence; Moore, Erika (Frontiers in Cardiovascular Medicine, 2022)
Vascular inflammation mediated by overly activated immune cells is a significant cause of morbidity and mortality in systemic lupus erythematosus (SLE). Several mouse models to study the pathogenesis of SLE are currently in use, many of which have different mechanisms of pathogenesis. The diversity of these models allows interrogation of different aspects of the disease pathogenesis. To better determine the mechanisms by which vascular inflammation occurs in SLE, and to assist future researchers in choosing the most appropriate mouse models to study cardiovascular complications in SLE, we suggest that direct comparisons of vascular inflammation should be conducted among different murine SLE models. We also propose the use of in vitro vascular assays to further investigate vascular inflammation processes prevalent among different murine SLE models.